Surface Wave Propagation on Carbon Nanotube Bundle and Characteristics by High Attenuation (Bulletin of Pure and Applied Sciences – Physics, 2021)
We have studied the surface wave propagation on carbon nanotube bundle and its  characteristics by high attenuation. The slow wave propagation along conducting carbon  nanotubes and the high conductivity compared with metallic conductors like copper made  these structures for high frequency applications. The property reduced the size of antenna and  passive circuits. It was found that the complex surface wave propagation has a significant  attenuation coefficient at lower frequency band. This attenuation coefficient induces highly  damping effect which reduces the active part of the dipole length. Thus, dipole lie always  below resonance and input impedance be always capacitive. The conductivity and  electromagnetic wave interaction of the conducting carbon nanotubes have also important  features in comparison with traditional conductors like copper wires of the same size. The  quantum capacitances of the order of the electrostatic capacitance of the transmission line.  This property has two main effects on electromagnetic wave propagation along the carbon  nanotube transmission line, slow wave propagation and high characteristic impedance. The  wave propagation on the arms of the dipole is highly attenuated such that the active part of  the dipole is such smaller than the physical length of the dipole itself. Thus, the dipole always  be a short dipole and could not be resonant in any case. The result shows that the advantage  of size reduction combined with surface wave propagation is used only in high frequency  bands above 100 GHz. The attenuation coefficient has a moderate effect in the frequency  band from 10 to 100 GHz. The resonance mechanism occurred when the incident wave at the  feeding point adds constructively with reflected wave from dipole ends. The obtained results  were found in good agreement with previously obtained results.